The Concept of Collaborative Learning Strategies and Their Relevance in Creating an Innovative Learning Environment in Islamic Religious Education Learning - Supardi Ritonga; Nurasikin Pratiwi; Ayu Ayu (World Journal of Islamic Learning and Teaching, 2024)
The implementation of collaborative learning strategies in Islamic religious education (PAI) subjects aims to create a learning environment that is innovative, interactive, and relevant to the needs of students in the digital era. The purpose of this research is to determine the implementation of collaborative learning strategies in creating an innovative learning environment in PAI subjects, the challenges in implementing collaborative learning strategies in PAI lessons, and to determine the use of technology in collaborative learning strategies to create innovative learning environments in PAI subjects. . The results of this research show that collaborative learning strategies in Islamic Religious Education (PAI) create an innovative and interactive learning environment. Methods such as discussions, case studies, and collaborative projects help students apply Islamic values ​​in real life. The implementation of collaborative learning strategies in Islamic Religious Education (PAI) faces challenges such as classroom management, curriculum adjustments, evaluation, and individual differences between students. And the use of technology in PAI collaborative learning creates an innovative and interactive learning environment. Bold platforms and visual media increase student engagement, understanding and digital skills, while teachers create dynamic learning. Technology supports more effective and relevant PAI learning.